Methodology of studies for selecting engineering decisions in territory planning - Priymachenko, Oleksiy; Kobzar, Oleksandr (KNUCA, 2018)
The vigorous growth of cities and reduction of free territories for building construction necessitate the development of town areas with complex geotechnical conditions. The complexity of construction in such areas causes increase of construction costs and, as a result, decrease of profitability in the real estate market and occurrence of additional risks in developing the corresponding areas. In the initial stage of design, that is, in the stage of technical-and-economic assessment, there is a need to select engineering planning decisions and to adopt the corresponding arrangement of engineering protective structures in the design area. Unavailability of an algorithm for solving this problem in the initial design stage often causes a need for redesign and for development of several design variants, and as a result, for increase of design periods and for attraction of additional costs. For this purpose, it is required to analyze factors affecting selection of engineering protective structures and use of such structures in certain development areas, as well as to develop an information model for selecting engineering protective structures for specific territories. The practicability of anti-landslide measures is determined with consideration for the basic causes of landslides. Therefore, the priority task is to determine the causes and types of landslides. Landslide protective structures selected with consideration for causes and types of landslides and in the next study stage is to determine the loads. The selection of optimal landslide protective structures is based on the results of engineering-geological studies and on the results of comparison of several design variants. Exactly, in selecting landslide protective structures required, models can be used. The engineering decision in territory planning should be taken by comparing variants of landslide protective structures with consideration for initial and calculated data. The proposed information model will provide the possibility to determine, in earlier design stages, the technology and cost of construction. The proposed methodology of studies for selecting engineering decisions in territory planning provides the possibility to predict the investment attractiveness of the development area and its profitability in the real estate market. The results obtained can be used in developing town-planning information bases for territories. The actuality of these studies is confirmed by development density and competition among builders in taking decisions and reducing risks.
Keywords: landslide; engineering protection of territories; anti-landslide measures; landslide protective structures; retaining wall; drainage